Al-Mahali Islamic Boarding School Administration Empowerment through Financial Management in Conformity with Accounting Standards - Enok Rusmanah; Amelia Rahmi; Fredi Andria; Jalaludin Almahali (Journal of Community Practice and Social Welfare, 2021)
Islamic boarding schools have an important role in Indonesia not only in developing religious knowledge but also in the building of character for the nation. With 26,000 schools in 2018 and around 4 million students recorded, Islamic boarding schools are among one of the various institutions in Indonesia that partake in the field of education. Islamic boarding schools also have a role in the country's economic development. However, regarding financial management as an educational institution, many Islamic boarding schools still utilise manual record-keeping methods. Such methods are currently insufficient to facilitate institutional development. The Al-Mahali Islamic boarding school is well aware of this issue and took the initiative to invite speakers from Economics Faculty of Pakuan University to share their knowledge on financial record-keeping in conformity with financial accounting standards (PSAK 45, SAK ETAP, and SAKSyariah). The knowledge-sharing program was held in an SAK based accounting training activity for the financial administration of Al-Mahali Islamic boarding school and students in general as a provision to expand their knowledge. The program was carried out smoothly and was greeted with enthusiasm by the participants. A follow-up mentoring session was planned to be held in the future regarding the implementation of SAK.